2006
DOI: 10.1002/art.21876
|View full text |Cite
|
Sign up to set email alerts
|

Efficient new cationic liposome formulation for systemic delivery of small interfering RNA silencing tumor necrosis factor α in experimental arthritis

Abstract: Objective. Tumor necrosis factor ␣ (TNF␣) is among the most prominent cytokines in rheumatoid arthritis (RA) and is secreted mainly by macrophages. A direct method for restoring the immunologic balance in RA is use of small interfering RNA (siRNA) for silencing the TNF␣ transcript. The aim of this study was to determine the therapeutic effect of systemic administration of TNF␣ siRNA in an experimental model of RA, optimizing its delivery using new liposome formulations.Methods. Murine macrophages were transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(112 citation statements)
references
References 38 publications
4
108
0
Order By: Relevance
“…39 To address in vivo the effect of TAK1 silencing in CIA as a prototype model of RA, we took advantage of a simple, efficient RNAi-based lipoplex formulation that we previously developed. 24 Although RNAi has emerged as a potent technology for silencing gene expression, the use of RNAi-based therapeutics has to overcome major obstacles, mainly effective delivery to target cells. We have previously demonstrated that the cationic liposome, RPR209120/DOPE, in combination with a carrier DNA, and siRNAs, provides high nucleic acid stability and effective lipofection rates at low amounts of formulated siRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39 To address in vivo the effect of TAK1 silencing in CIA as a prototype model of RA, we took advantage of a simple, efficient RNAi-based lipoplex formulation that we previously developed. 24 Although RNAi has emerged as a potent technology for silencing gene expression, the use of RNAi-based therapeutics has to overcome major obstacles, mainly effective delivery to target cells. We have previously demonstrated that the cationic liposome, RPR209120/DOPE, in combination with a carrier DNA, and siRNAs, provides high nucleic acid stability and effective lipofection rates at low amounts of formulated siRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…capacities, we have previously shown that no type I IFN response could be observed upon intravenous injection of 0.5 mg/kg of unmodified siRNA duplexes formulated with our delivery system. 24,40,45 Different types of cells or tissues have been reported to be sensitive for TAK1 deletion and undergone apoptotic cell death. 19 Here, we show that targeted organs of TAK1-siRNA lipoplex-injected mice exhibited similar numbers of mononuclear cells, indicating that TAK1 RNAimediated knockdown does not induce cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, small interfering RNAs (siRNAs), 21-23 nucleotide-length fragments (Elbashir et al 2001;Hannon 2002;Xie et al 2006), have been shown to be of great value in decreasing the expression of the target gene by in vivo administration (Song et al 2003;Nakamura et al 2004;Schiffelers et al 2005;Khoury et al 2006) In the present study, we applied siRNA targeting to an OPN coding sequence (OPN-siRNA) to inhibit OPN function by reducing OPN expression. We demonstrate the remarkable efficacy of OPN-siRNA to prevent EAU in mice.…”
Section: Introductionmentioning
confidence: 99%
“…However, their in vivo application requires effective delivery to immune cells and/or sites of inflammation (28). Recent efforts to facilitate systemic oligonucleotide delivery to inflammation sites in vivo have included the use of neutral liposomes (17) or atelocollagen (29) in experimental allergic dermatitis, cationic liposomes in experimental arthritis (30), and antibody-targeted stabilized nanoparticles in experimental colitis (31).…”
Section: Discussionmentioning
confidence: 99%